The Aristophane’s speech in Plato’s symposium - Menezes, Luiz Maurício Bentim da Rocha (Argumentos - Revista de Filosofia, 2025)
Plato’s Symposium is about Love (Eros) par excellence. Our work will focus on the discourse uttered by Aristophanes that, in order to speak of all the possible loves among men, will make what would be the first myth about gender, that is, the myth of the androgynous. It will be through this myth that it will be possible to establish a sense for the fullness of love between men or, as we prefer to say, an erotic whole that is formed from the division of humanity into three different genres. Aristophanes, in this way, manages to demonstrate the meaning of love in the widest possible way. At the end, aristophanic discourse will be confronted with the defense of the love given by Socrates and the relation he establishes between the erotic whole and the Good.